Evaluation of a Rapid Kit for Detection of IgM against Leptospira in Human. (7th February 2019) - Rao, Mohan; Amran, Fairuz; Aqilla, Nadia
Abstract : Introduction . Leptospirosis is an acute febrile illness, known for its protean clinical manifestations and the challenge in differentiating from other infectious diseases. Standardized confirmatory test is antibody dependent and not accessible by the suburban community. This study measures efficiency of an immune-chromatographic assay, Leptocheck WB, in detecting acute leptospirosis. Methods . A total of 142 sera were used for kit evaluation. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated by comparing rapid kit results with gold standard laboratory, microscopic agglutination test (MAT). Results . We found this rapid kit to have a sensitivity and specificity of 66.6% and 78.9%, respectively, whereas the PPV and NPV of the kit appeared to be 73.3% and 73.2%, respectively. Discussion . Test efficiency of this rapid kit is reasonable. It is specific in detecting leptospiral antibody and assures clinician of accurate diagnosis by having higher PPV and NPV. It is prompt and efficient in comparison with conventional methods in assisting differential diagnosis. High sensitivity and specificity leptospirosis rapid test is indeed a crucial measure to assist the diagnosis of acute undifferentiated febrile illnesses.